Development of 3-D numerical methodology to investigate transient characteristics of fuel temperature and hydrated residual water during drying process of dry storage system. (July 2022) - Tseng, Y.S.; Wang, W.Y.; Lin, C.H.; Ferng, Y.M.; Wan, M.H.
Highlights: A 3-D numerical methodology is developed to model water drying process for DSS. Effects of burnup and thermal loading on the drying process are considered. Burnup effect is insensitive on the SNF temperature and drying ratio. Lower thermal loading must be conservatively used to evaluate the drying process. Elevating ambient temperature is useful ways to improve the drying efficiency. Abstract: The dry storage system (DSS) is the most popular method for the interim storage of spent nuclear fuels (SNFs). The internal environment with high humidity and radiation would induce radiolysis and recombination, degrading the internal components and SNFs within the DSS during the storage period. A three-dimensional (3-D) transient heat transfer methodology is developed to model the hydrated residual water in drying process for the DSS. Effects of thermal loading and fuel burnup on SNF temperature and residual water are also considered. Based on the comparison, effects of burnup on the SNF temperature and the drying ratio are insignificant. More hydrated water is retained on the fuel surface for the lower thermal loading. Present simulation results strongly recommend that the lower thermal loading should be used to evaluate the drying process in order to avoid the unexpected residual water retained on the fuel surface in any one DSS.